Serological Investigation of Human Cystic Echinococcosis and Associated Risk Factors in the At-risk Population of Northeast Iran in 2018-2019 - Mitra Salehi; Akbar Solati; Ahmadreza Atarodi; Jafar Hajavi; Hossein Nezami (Gonabad University of Medical Sciences, 2024)
Background: Hydatidosis is a leading zoonotic parasitic disease causing economic losses and public health concerns worldwide. The current study aims to determine the seroepidemiological status of hydatid cysts (HCs) and assess the relationship between risk factors and this disease in high-risk individuals in Gonabd City, Iran. Methods: This cross-sectional study was conducted in Gonabad health centers in 2018-2019. Sampling was performed using the census method. A total of 393 serum samples were collected from 259 men and 134 women at risk for HC. A questionnaire was prepared for all participants. Demographic information, such as gender, age, place of residence, education level, participation of children in animal husbandry, the way of washing vegetables, and work experience in animal husbandry were recorded. The levels of immunoglobulin G (IgG) antibodies were measured by enzyme-linked immunosorbent assay (ELISA). Results: The infection rate was 9.7% for men and 10% for women, showing no significant correlation between gender and hydatidosis. Among the affected population, the prevalence rate was 10.4% in undergraduates and 16.3% in the age group of 20-30. Additionally, individuals with less than ten years of experience in animal husbandry had a prevalence rate of 11.7%. Those who had contact with dogs had a prevalence rate of 7.9%, while individuals who did not use disinfectants to wash vegetables had a higher rate of 12%. Conclusion: This study highlights the significant prevalence of HCs in at-risk individuals. This indicates the need for effective preventive measures to reduce the burden of infection. The recommendations include washing vegetables with disinfectants to eliminate any potential sources of contamination. Additionally, obtaining identification certificates for livestock dogs and collecting stray dogs can help control the spread of the disease. It is essential to implement a comprehensive public health strategy to address this issue effectively.